Relationship between grades in some selected high school subjects and performance in physics - Rivera, Eustaquia De La Paz 1944- (1978)
This study investigated the relationship between grades in some high school subjects and performance in Physics of students of the Dona Aurora High School, San Mateo, Rizal during the school year 1976-1977. The subjects consisted of 224 fourth year students who were enrolled in the school since their first year. Pearson's Product Moment Correlation was used to quantify the degree of linear relation between the variables under study. The results showed that there existed substantial or marked to very high relationship between each of the individual subjects and performance in Physics. Math has the highest correlation, followed by Science, then English. Students whose grades are high in English, Math or Science subjects in their first 3 years tend to perform well in Physics.
Vita.
Thesis (M.A. Physics Education)--University of the Philippines, Diliman.
Keywords: Physics -- Study and teaching (Secondary) -- Philippines -- San Mateo (Rizal); High school students -- Rating of -- Philippines -- San Mateo (Rizal); Academic achievement -- Philippines -- San Mateo (Rizal)